Exploring efl pre-service teachers’ experience with cultural content and intercultural communicative competence at three colombian universities (2013)
This article reports the findings of a qualitative research project that explored pre-service English teachers’ perceptions of and attitudes toward the aspects of culture and intercultural competence addressed in their English classes in the undergraduate programs at three Colombian universities. Findings reveal that pre-service teachers are mainly taught elements of surface culture and lack full understanding of intercultural competence. They also see culture as a separate aspect of their future teaching career. We provide alternatives so that pre-service teachers might overcome limitations of the teaching of culture as preparation for their future teaching career in the foreign language classroom.Este artículo reporta los hallazgos de una investigación cualitativa que indagó sobre las percepciones y las actitudes de los profesores en formación en el área de inglés respecto a los contenidos culturales y la competencia cultural que se abordan en las clases de inglés, en tres universidades colombianas. Los hallazgos revelan que los docentes en formación primordialmente tratan aspectos de la cultura superficial y no tienen total claridad de qué es la competencia comunicativa intercultural. También conciben la cultura como un aspecto desligado de su futura profesión docente. Se sugieren algunas alternativas para que los profesores en formación puedan superar las limitaciones de la enseñanza de la cultura y se preparen para su futura carrera docente en el salón de inglés como lengua extranjera.